Isolation and identification of potential probiotic lactic acid bacteria (Lactobacillus casei and Bifidobacterium) from raw and fermented camel milk during storage - Malini, N S; Raghav , Pramod K. (Journal of Postharvest Technology, 2021)
The aim of this study is to isolate and molecularly characterize LAB present in raw and fermented milk. The sample was collected in local areas in Jaipur Rajasthan. The identification of the selected LAB strains and their genetic relatedness was performed based on 16S rDNA gene sequence comparisons. They differed in their different probiotic characteristics such as tolerance to acidic pH, resistance to bile tolerance, and antibacterial activity. In conclusion, the isolates Lactobacillus casei, Enterococcus durans, Lactobacillus Plantarum, and Bifidobacterium were most probably high quality with probiotic potentials. We speculate studying the synergistic effects of bacterial combinations might result in a more effective probiotic potential, Lactobacilli species (42.90%). Enterococcus spp isolates represented 28.26%, The remaining isolates were Lactobacillus casei and Bifidobacterium that represented 4.87% and 2.42%. We suspect in raw and fermented camel milk was rich in LAB and has capable probiotic potential.